Re-thinking patient motivation in clinical rehabilitation encounters: insights from different theoretical perspectives. Issue 1 (2nd January 2021) - Papadimitriou, Christina; Caddick, Nick; Stone, David A.
ABSTRACT: We use analytic pluralism to discuss and analyze a data excerpt from the medical rehabilitation of an inpatient with spinal cord injury and his physical therapist to examine how the concept of motivation is used in clinical practice. We employ three theoretical perspectives in order to explore ways of understanding this concept: Social Determination Theory, Phenomenology, and Narrative Inquiry. We present and argue for multiple ontologies as a new way forward to understanding complex human phenomena such as motivation.